Evaluating the impact of a participatory organizational intervention on reducing occupational stress in an emergency department setting: a one group pretest-posttest design - Hendrik Van Simaeys; Lore Mannaerts; Brecht Serraes; Els Clays (BMC Public Health)
Abstract Background Occupational stress among healthcare professionals, especially those in emergency departments, is associated with high job demands and inadequate resources, impacting both service delivery and worker well-being. This study explored a participatory organizational intervention intended to reduce stress and improve working conditions among emergency department staff. Methods A one-group pretest‒posttest design was used to examine changes in outcomes among healthcare professionals (n = 59). Standardized self-report questionnaires administered before and after the intervention assessed perceived stress levels, psychosocial work factors, and general satisfaction. The nine-week intervention consisted of structured group discussions to identify stressors and co-develop solutions, followed by targeted adjustments in work processes and the environment. The primary outcome was perceived stress (Perceived Stress Scale-10, PSS-10). Secondary outcomes included working conditions (Danish Psychosocial Work Environment Questionnaire, DPQ). Paired samples t-tests compared pre- and posttest scores, and Pearson correlations assessed associations between process indicators and changes in perceived stress. Results Postintervention findings indicated a marginally significant reduction in perceived stress and improvements in several aspects of the psychosocial work environment, including work‒life balance and supervisory recognition. These results suggest that the participatory intervention may be associated with improvements in the perceived work environment. Process evaluation results indicated moderate employee engagement, with generally positive perceptions of involvement and overall satisfaction. A marginally significant negative correlation was found between employee involvement and stress reduction, suggesting that greater involvement was associated with greater decreases in perceived stress. Conclusions While the absence of a control group limits causal inference, the study offers exploratory evidence that participatory organizational approaches may be linked to perceived improvements in staff well-being and working conditions in emergency care settings. Further research using comparative designs is needed to confirm these preliminary findings and to better understand how participatory interventions might contribute to workforce sustainability in healthcare.